Environmental niche modelling fails to predict Last Glacial Maximum refugia: Niche shifts, microrefugia or incorrect palaeoclimate estimates? - Worth, J.; Williamson, G.; Sakaguchi, S.; Nevill, Paul; Jordan, G. (Blackwell Publishing Ltd, 2014)
Aim: Many predictions of responses to future climate change utilize ecological niche models (ENMs). We assess the capacity of these models to predict species distributions under conditions that differ from the current environment by testing whether they can predict past distributions of species. Location: From 43°S to 31°S in south-eastern Australia (including Tasmania). Methods: We studied three dominant tree species of temperate Australian mesic forests, Atherosperma moschatum, Eucalyptus regnans and Nothofagus cunninghamii. Phylogeographic evidence indicates that these species each survived the Last Glacial Maximum (LGM) in multiple refugia. We modelled the current distribution of each species and projected those models onto LGM climates under six palaeoclimatic scenarios. The support for phylogeographic-based glacial refugia was estimated under each scenario using three different thresholds for inferring species presence/absence. Results: The LGM models under scenarios that allowed for a realistic level of rainfall failed to predict survival of the study species in refugia identified from genetic evidence, apart from those in perhumid western Tasmania.Main conclusions: Correct prediction of nearly all modern occurrences of the species suggests that this failure of ENMs to predict refugial survival was not methodological. Rather we conclude that the existing realized niches of these species may have changed since the LGM. Such niche changes may have involved the occurrence of non-analogue climates in the LGM and some significant alteration of fundamental niche (for at least E.regnans). Our results emphasize that predictions of future impacts of climate change on biodiversity will benefit from awareness of the limitations of ENMs in predicting the extinction of populations/species. Greater knowledge of how niches have changed through time and how this relates to the characteristics of species is needed to improve the reliability of ENMs. Niche changes in plants may also affect palaeoclimatic estimates based on fossil pollen.